Finance and Development, March 1983. (Finance and Development; Finance and Development ;, 1983)
This paper examines the policy of protectionism in world trade. It reviews alternatives to trade restrictions, factors influencing trade policies, and implications of protection for developing countries. The paper highlights that the rise in protectionist pressures is worrisome, because the likelihood of chain reactions toward more protectionism generated by individual restrictive actions is greatest in a setting of slow economic growth and highly interdependent economies. The paper also analyzes capital utilization in the manufacturing enterprises.